Paradigms of Risk, Hazards and Danger - Panik D. E. (Modern trends in management, economics and business: from theory to practice, 2023)
In his 1962 work The Structure of Scientific Revolutions, Thomas Kuhn defined a paradigm as a set of concepts that form the foundations of a scientific field. He presents revolutions as shifts in existing paradigms, and the phrase "paradigm shift" has since entered the language of science and business. Risk is a concern in both science and business, and this chapter examines paradigms of risk and whether a shift is needed. Despite our avoidance of negative experiences that are often interpreted as the result of hazards, there is no general methodology for managing risk. This statement may seem wrong: after all, safety is a broad field; we analyse hazards and manage risks. But isn't this an illusion, and isn't risk management an attempt to charm reality? Aren't hazards, risk and threat dependent on our perception? Perhaps risk can be viewed through the lens of quantum mechanics, existing in a state of potentiality until our actions and interpretations force events and circumstances into
Keywords: опасность; угроза; риск; risk; парадигмы; hazards; dange; paradigms